THE CORRELATION OF THE TENTH GRADE STUDENT’S VOCABULARY MASTERY AND READING COMPREHENSION AT SMA NEGERI 6 TANGERANG - Nofia Nofia (Universitas Muhammadiyah Tangerang, 2019)
Vocabulary, which consists of the knowledge of meaning as the main component of a language, should be taught together with reading, structure and conversation. This research conducted to know whether there is any correlation between vocabulary mastery and reading comprehension among tenth grade students of SMA Negeri 6 Tangerang. Those students has different background and interest which impact to learning and teaching process especially in reading activity. The sample of this research involving 68 students and carried out quantitatively with tests as instruments and questionare. The result of table correlation shows that the significance is ρcount 0,050 and ρtable 0,77. It means 0,799 > 0,050. It means that the correlation between vocabulary mastery and reading comprehension is positive and not significant. Suitable and appropriate technique, test and method needed.